EXPLORING THE ROLE OF BRAND AMBASSADORS IN SHAPING BRAND EQUITY: INSIGHTS FROM THE BEAUTY SECTOR - Sitti Hasbiah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This study aims to examine the relationship between brand ambassadors and brand equity in the beauty industry, focusing on Somethinc, an Indonesian skincare brand. Using a quantitative research approach, data were collected through surveys distributed to 45 respondents who are followers of Somethinc's Instagram account. The analysis employed path analysis and various statistical tests, including normality, multicollinearity, and heteroscedasticity tests, to ensure the robustness of the results. The findings revealed a significant positive relationship between brand ambassadors and brand equity, with the model explaining 48% of the variance in brand equity. Specifically, the presence of a brand ambassador significantly influenced consumer perceptions, contributing to increased brand loyalty, brand awareness, perceived quality, and brand associations. This study highlights the importance of strategic celebrity endorsements in enhancing brand equity, particularly in the competitive beauty sector. The results contribute to a deeper understanding of how brand ambassadors can be leveraged to strengthen brand positioning and consumer trust.